XtalCAMP: a comprehensive program for the analysis and visualization of scanning Laue X‐ray micro‐/nanodiffraction data. Issue 5 (23rd September 2020) - Li, Yao; Chen, Kai; Dang, Xiaofeng; Zhang, Fengying; Tamura, Nobumichi; Ku, Ching-Shun; Kang, Huijun; Wenk, Hans-Rudolf
Abstract : XtalCAMP is a MATLAB‐based software package suitable for the analysis and visualization of scanning Laue X‐ray micro‐/nanodiffraction data. The graphical user interfaces allow the easy analysis of characteristic microstructure features, including real‐time intensity mapping for a quick examination of phase, grain and defect distribution, 2D color‐coded mapping of crystal orientation, principal strain/stress analysis, and strain ellipsoid representation, as well as a series of additional toolkits. Abstract : XtalCAMP is a software package based on the MATLAB platform, which is suitable for, but not limited to, the analysis and visualization of scanning Laue X‐ray micro‐/nanodiffraction data. The main objective of the software is to provide complementary functionalities to the Laue indexing software packages used at several synchrotron beamlines. The graphical user interfaces allow the easy analysis of characteristic microstructure features, including real‐time intensity mapping for a quick examination of phase, grain and defect distribution, 2D color‐coded mapping of microstructural properties from the output of other Laue indexing software, crystal orientation visualization, grain boundary characterization based on orientation/misorientation calculation, principal strain/stress analysis, and strain ellipsoid representation, as well as a series of additional toolkits. As an example, XtalCAMP is applied to the microstructural investigation of a solution‐heat‐treated Ni‐based superalloy manufactured using a laser 3D‐printing technique, and a deformed natural quartzite from Val Bregaglia in the Central Alps.